SELFPERCEPTION OF THE BODY IMAGE AND THE MEANING OF THE BODY IMAGE IN ACTIVE PRACTICING OF THE ACADEMICS OF PHYSICAL EDUCATION OF CARIRI REGION IN CEARÁ STATE. (Fiep Bulletin - online, 2013)
It is indispensable that the teacher of Physical Education hás his body image (IC) well developed, because it will contribute at conscience of the meaning of the body manifestations, in your active practice. Our aim was to analyse the self-perception of the body image of academics of graduatíon of Physical Education of Cariri region and the meaning of the body image (IC) in its active practice. Methodology: The research was characterized like quantitative, the sample was formed by seventy seven academics, forty men (27,08 + 6,41) and thirty seven women (24,05 + 3,42). We had evalueted the self perception of the Ic through of the silhouette scale introduced by stunkard et al apud tritscheler (2003 p. 461). We used a subjective question about the influence of the IC in active practice for provocate a discussion more useful about the theme. We had introduce the results through of percentage charts and we had compared the answers with the pertinent literature related the theme. Results: Related the perception of the IC in referent to appearance physical actual the group had identified by itself like the silhouette of numbers 3, in second inquiry the physic appearance that would like to have, the men has identified themselves with the silhouette three and the women with the two, in third question the physic appearance that they had there was one year the manly group didn't introduce difference af image, while that the women had introduced a insatisfation with the image. And related the subjective question, the group had affirmed that the image influences in active practice. It is important that the professional futures in your active practice, they understand that, should have a working with the appearance, with it, for that the pupils instead to look at the appearance, enjoy our capability like a respectable professional, ethic and that know several matters.
Keywords: Physical Education; body image; active practice